Characteristics of Kidney Failure Patients in Sardjito Hospital Yogyakarta - Nuni Ihsana; Dewi Yuniasih; Barkah Purwanto (Universitas Ahmad Dahlan, 2020)
Chronic kidney disease (CKD) has become a serious public health problem. The aim of this study was to identify the characteristics of patients at high risk of developing kidney failure. The research subjects were analyzed as many as 57 subjects, showing that male sex (61.4%) suffered more from CKD than women (38.6%). The mean age was 37.84 Â± 16.16 with a median length of Â Continuous Ambulatory Peritoneal Dialysis (CAPD) of 36 months. Our study found 45.6% of the patients had an undergraduate degree, followed by 38.6% of the patients had a high school education. Further analysis is needed with more age groupings so that the characteristics of patients with kidney disease (CKD) can be known in detail from various elements of society.Â